Load Flow Analysis of 132 kV Transmission Line with Optimally Terminated Service Potential Transformer Substations - Kitheka, Joel Mwithui; Moses, Peter Musau; Nyete, Abraham Mutunga; Abungu, Nicodemus O. (MSD Institute, 2025)
Most villages in Sub-Saharan Africa still lack electricity, despite numerous initiatives and commissions established to address power demands in developing countries. Renewable energy, rural electrification, and non-conventional substations are currently being employed to tackle the electricity issue. This research explored the penetration level of Service Potential Transformer (SPT) substations to solve the lack of electricity in villages near high-voltage transmission lines. The study analyzed the power flow in the 132 kV Juja-Rabai transmission line using PowerWorld Simulator software and determined the optimal termination points for SPT substations. Cost minimization was used as the objective function. At the same time, the voltage profile of the transmission line, the power demand of households, and the distance of villages from the transmission line served as the research constraints. The findings indicated that seven SPT substations could be installed along the 132 kV Juja-Rabai transmission line to supply electricity to nearby villages. These non-conventional substations would be integrated with the existing conventional substations on the transmission line. The power flow analysis for the line was also conducted.